2013
DOI: 10.1177/1363459313501358
|View full text |Cite
|
Sign up to set email alerts
|

‘It seemed churlish not to’: How living non-directed kidney donors construct their altruism

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent repository link Jay WattsUniversity of London, UK AbstractOur objective was to explore how prospective altruistic kidney donors construct their decision to donate. Using a qualitative design and biographical-narrative semistructured interviews, we aimed to produce text for analysis on two levels: the social implications for subjectivity and practice and a tentative psychodynamic exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 32 publications
1
28
0
Order By: Relevance
“…20,21 This may represent a response that is highly influenced by the psychological benefits of donation. 22,23 The finding illustrates the important interplay between patient characteristics and individual domains of pain perception. This observation argues against opinion that the only way to improve pain management is the strict use of protocols for monitoring and administering analgesics.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…20,21 This may represent a response that is highly influenced by the psychological benefits of donation. 22,23 The finding illustrates the important interplay between patient characteristics and individual domains of pain perception. This observation argues against opinion that the only way to improve pain management is the strict use of protocols for monitoring and administering analgesics.…”
Section: Discussionmentioning
confidence: 80%
“…In-depth qualitative analysis has shown “discouraging donation” produces interpersonal stress and emotional distress due to conflict with social ties. 23,31 It is possible that social conflict due to disagreement about donation could lead to emotional distress that is expressed in response to pain.…”
Section: Discussionmentioning
confidence: 99%
“…Clarke et al () however have indicated that there are stages within the donation procedure that are experienced as difficult for the donor and may influence their commitment to continue with donation. A significant potential barrier includes negative evaluations of their decision from members of their primary social group (PSG), peers and healthcare professionals (Jacobs et al ; Massey et al ; Clarke et al ; Challenor & Watts ). The PSG has been defined as a network of relationships characterised by extensive interaction, strong emotional ties, and endurance over time (Cooley ).…”
Section: Introductionmentioning
confidence: 99%
“…The PSG can therefore include both family members and those with whom donors have close friendships. UKDs often reported encountering scepticism and resistance from members of their PSG (as well as wider community members) and described needing to be determined to overcome such resistance to proceed to donation (Clarke et al ; Challenor & Watts ). Furthermore, disapproval from ‘key others’ has been highlighted as a barrier to living donation in general (Hyde & White ).…”
Section: Introductionmentioning
confidence: 99%
“…31 Non-directed altruistic donors, much like directed donors, report being motivated by a desire to benefit other people or society as a whole, a compelling desire to donate and recognise personal psychosocial gains. [32][33][34] Where commercial organ trading exists, or where donation is financially incentivised, most unrelated donors report financial motivation. [35][36][37][38] Payment for donation is illegal in almost all countries.…”
mentioning
confidence: 99%